2018
DOI: 10.1136/bmj.k3851
|View full text |Cite
|
Sign up to set email alerts
|

Use of N-nitrosodimethylamine (NDMA) contaminated valsartan products and risk of cancer: Danish nationwide cohort study

Abstract: ObjectiveTo perform an expedited assessment of cancer risk associated with exposure to N-nitrosodimethylamine (NDMA) through contaminated valsartan products.DesignNationwide cohort study.SettingDanish health registries on individual level prescription drug use, cancer occurrence, and hospital diagnoses.Participants5150 Danish patients with no history of cancer, aged 40 years or older, and using valsartan at 1 January 2012 or initiating use between 1 January 2012 and 30 June 2017. Participants were followed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…7,8 The International Agency for Research on Cancer has classified NDMA as a probable carcinogen, with animal studies finding tumor formation predominantly in the gastrointestinal tract and liver but also in the lungs and kidneys. 8,9 NDMA, like other nitrosamine contaminants, activates ras oncogenes, and NDMA metabolism by CYP2E1 creates methyldiazonium, a known mutation inducer via methylation. [8][9][10] As such, NDMA is suspected to cause both localized and systemic carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The International Agency for Research on Cancer has classified NDMA as a probable carcinogen, with animal studies finding tumor formation predominantly in the gastrointestinal tract and liver but also in the lungs and kidneys. 8,9 NDMA, like other nitrosamine contaminants, activates ras oncogenes, and NDMA metabolism by CYP2E1 creates methyldiazonium, a known mutation inducer via methylation. [8][9][10] As such, NDMA is suspected to cause both localized and systemic carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 NDMA, like other nitrosamine contaminants, activates ras oncogenes, and NDMA metabolism by CYP2E1 creates methyldiazonium, a known mutation inducer via methylation. [8][9][10] As such, NDMA is suspected to cause both localized and systemic carcinogenic effects. 9,10 Where Does NDMA Come From?…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Metformin, NDMA and FDA recall A Dutch study reported last year that exposure to NDMA-contaminated medicines was associated with a small increase in risk for overall cancer (HR, 1.09; 95% CI, 0.85-1.41). 15 The HR increased to 1.46 for colorectal cancer and 1.81 for uterine cancer, although confidence intervals were wide. FDA currently recognizes the danger of this compound and, as a result, has set strict daily acceptable intake limits on NDMA in pharmaceuticals of 96 nano grams.…”
Section: Ndma and Cancer Riskmentioning
confidence: 96%
“…The contamination is in all likelihood related to a change in the manufacturing process in Zhejiang Huahai Pharmaceuticals in 2012. 9,10) Sodium azide and N,N-dimethylformamide (DMF) were used for the formation of the tetrazole ring in valsartan. Subsequently, excess sodium azide, remaining after the formation of the tetrazole ring, was quenched with sodium nitrite under acidic conditions, resulting in the formation of nitrous acid.…”
Section: Introductionmentioning
confidence: 99%